1995
DOI: 10.1029/94jd03245
|View full text |Cite
|
Sign up to set email alerts
|

Dust deposition in southern Nevada and California, 1984–1989: Relations to climate, source area, and source lithology

Abstract: Dust samples collected annually for 5 years from 55 sites in southern Nevada and California provide the first regional source of information on modern rates of dust deposition, grain size, and mineralogical and chemical composition relative to climate and to type and lithology of dust source. The average silt and clay flux (rate of deposition) in southern Nevada and southeastern California ranges from 4.3 to 15.7 g/m2/yr, but in southwestern California the average silt and clay flux is as high as 30 g/m2/yr. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
279
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(304 citation statements)
references
References 56 publications
(41 reference statements)
14
279
1
Order By: Relevance
“…Yet a growing body of literature reveals that vegetated landscapes and dune fields can emit dust [Bullard et al, 2008;Rivera Rivera et al, 2009] (Figure 1). Recent advances using satellite data over northern Africa have also shown that dust sources may be more diverse than previously believed [Schepanski et al, 2007], and in the Mojave Desert of the southwestern United States, alluvial fans and plains may be larger overall contributors to total dust emission than dry lakes [Reheis and Kihl, 1995].…”
Section: Where Does Dust Come From?mentioning
confidence: 99%
“…Yet a growing body of literature reveals that vegetated landscapes and dune fields can emit dust [Bullard et al, 2008;Rivera Rivera et al, 2009] (Figure 1). Recent advances using satellite data over northern Africa have also shown that dust sources may be more diverse than previously believed [Schepanski et al, 2007], and in the Mojave Desert of the southwestern United States, alluvial fans and plains may be larger overall contributors to total dust emission than dry lakes [Reheis and Kihl, 1995].…”
Section: Where Does Dust Come From?mentioning
confidence: 99%
“…M any studies have addressed the presence of aeolian dust in soils and surficial deposits in deserts to provide important geologic and ecologic information bearing on landscape dynamics (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). From this body of work, we have improved understanding about: (i) current and past sources and flux of dust, hence changing conditions of dust emission; (ii) the genesis of desert soils; (iii) the influences of aeolian silt and clay on water-infiltration rates in soil; (iv) the evolution of desert surfaces (such as desert pavement) relevant to surface stability, as well as the distribution of surface and subsurface water; and (v) interrelations among aeolian dust, distribution of plants and soil crust, rain-water runoff, and productivity.…”
mentioning
confidence: 99%
“…Shuwaikh city (Kuwait), based on this study, followed Bina of India in dust fall with an average amount of 53.7 ton km -2 month -1 , which is indeed expected as it is located in an arid region, and it is located within one of the five major regions where dust originates. Areas in North and Northwest India exhibited intermediate value (21 ton km -2 -month -1 ) of dust fall (Yadav and Rajamani 2006), followed by Nagev desert (Offer and Goossen 2001), Lanzhou (Liu et al 2004), Texas (Crabtree 2005), Yazd (Naddafi et al 2006), Arizona (Crabtree 2005), California (Crabtree 2005), and Southern Nevada (Reheis and Kihl 1995), as shown in Fig. 5.…”
Section: Comparison Of Dust Fall Levels With Other Citiesmentioning
confidence: 99%